Business Development Using Business Model Canvas in Lucky Star Digital Printing - Aviora Karunia; Bustanul Arifin (Institut Teknologi Sepuluh Nopember, 2019)
Large amount of the demands for branding and spreading the information makes the business of digital printing dominate the market needs. Lucky Star located in Cepu has been operating for 5 years. Unfortunately, they do not have the right business model. To collect the data was obtain from Focus Group Discussion (FGD). Questions asked on FGD were directed to gain knowledge about the owner and employees’ wants, also customers needs. Afterwards, the data were classified according to the categories of BMC. The researcher offered BMC hope that it can lead the business become market leader. Business model Canvas is validated using the javelin board to show that problems and the solutions are correct. The results of this study indicate that customer segments must be determined with STP (Segmenting, Targeting, Positioning) strategy. The additional value proposition is create a promo, bundling products, and add delivery services. the best channel is the